Oxidation protection of SiC in porcelain tile ceramics by adding Si powder. Issue 7 (July 2017) - Xi, Xiuan; Xiong, Hao; Zou, Canhui; Zuo, Fei; Huang, Rongxia; Lin, Hua-Tay
Abstract: Polishing porcelain tile residues (PPR) have accumulated to millions of tons and increases every year. It has become important to recycle the PPR due to the economic gains and environmental sustainability of doing so. However, its direct recycling in the production of porcelain tile has been limited by the fact that SiC particles oxidise during sintering which prevents the processing of dense ceramics. In this study, Si powder was introduced into the porcelain ceramics matrix containing SiC. The effect of Si powder additive on inhibiting the oxidation of SiC was evaluated using the relative density and the microstructure of the sintered samples. Results showed that the porcelain body containing SiC could be fully densitified when the suitable content of Si powder addition is introduced. These results indicate that it is a promising method to effectively protect the oxidation of SiC particles in the porcelain ceramics matrix during sintering.